Nematode diversity indices application to determine the soil health status of Lembo Agroecosystem in West Kutai, East Kalimantan Province, Indonesia - Suyadi SUYADI; SURYA SILA; JEMI SAMUEL (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Suyadi, Sila S, Samuel J. 2021. Nematode diversity indices application to determine the soil health status of Lembo agroecosystem in West Kutai, East Kalimantan Province, Indonesia. Biodiversitas 22: 2861-2869. Lembo is a typical agroecosystem developed by the people of East Kalimantan, especially in the West Kutai District. Lembo agroecosystems (LA) are generally built on the former of sifting cultivation rice fields. The fertile condition of tropical rainforest land in East Kalimantan, if converted to a rice field agroecosystem, its fertility decreases drastically. However, Lembo is an agroecosystem similar to the forest, and its soil health status in this study was determined by using nematode diversity indices as the indicator. Nematode diversity indices are very useful as indicators because nematodes occupy all positions of the micro food web in the rhizosphere. They can support the increase in soil fertility or pose risks as a pest. This study was aimed to determine the health status of LA soil by using evaluation indicators: (i) nematode absolute abundance, (ii) nematode diversity indices [Shannon-Wiener index (H'), genera richness index (GR), and dominance index (?)], and (iii) nematode maturity indices (?MI, MI, MI2-5, PPI, and the PPI/MI-ratio), and using the oil palm plantation (OPP) as the comparison agroecosystem. Based on nematode maturity indices, LA soil health status was categorized as good with MI value > 2.6, the community abundance of nematode genera in the colonizers' group (c-p2) ? 50%, and community abundance of nematode genera in the persisters group (c-p4) > 10%. Then based on the nematode diversity indices (H', GR, and ?), the LA soil health status was higher than the OPP soil health status, in LA the values of H', GR, and ? were 30%-43%, 60%-91%, and 12%-88%, respectively higher than OPP. The pest status of plant-parasitic nematodes in both agroecosystems is relatively light because their presence is counterbalanced by predatory, carnivore, and omnivore nematodes.